Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Depot Air Minum Isi Ulang Tompotika Water Luwuk: The Influence of Service Quality on Customer Satisfaction Tompotika Water Luwuk Refill Drinking Water Depot - Taufik Abdullah; Ichsan Milang; Yusnita Fitarini Sibay (Jurnal Ilmiah Produktif, 2023)
The aims of this research were (1) to find out how the effect of service quality on customer satisfaction at Tompotika Water Luwuk refill drinking water depots, (2) Which variables affect service quality on customer satisfaction at Tompotika Water Luwuk refill drinking water depots. The analytical method used in this study is multiple linear regression analysis using 100 samples taken using the Slovin technique. Based on the results of the research and testing it was concluded that the quality of service which consists of physical evidence, reliability, responsiveness, assurance, and empathy has a partial or simultaneous effect on customer satisfaction, while the independent variables are physical evidence, reliability, responsiveness, assurance, and empathy has a strong relationship to customer satisfaction, as well as the contribution of service quality variables consisting of physical evidence, reliability, responsiveness, assurance, and empathy to the dependent variable namely customer satisfaction is 62.1%, while the remaining 37.9% is caused by other factors that are not examined such as marketing mix, and product quality.